Towards a Manumissive Black Fantastic in Fandom, Fantasy, and Literature for Young People, or: A Case for the Black Hermione - Casey Wayne Patterson (International Journal of Young Adult Literature, 2022)
This article proposes a method for studying and engaging in a Black melancholic practice of YA SFF (science fiction and fantasy) fandom. In 2015, a minor fan discourse on ‘the Black Hermione’ rose to public prominence when the Black actress Noma Dumezweni was cast to play Hermione Granger in J.K. Rowling’s new Harry Potter stage play. I argue that the ensuing discourse evidences a fannish desire for authorial sanction that is underrecognized in the field of fandom scholarship. Race and melancholy both inflect experiences of fandom, but fandom studies historically lacks frameworks for considering either. Rowling’s public espousal of a trans-exclusive gender politic since 2019 has made it particularly urgent to address the disappointments and unrealized desires that inform fans’ relations with cultural creators. Though obscured in Rowling’s partial embrace of the Black Hermione, I argue that this 2015 episode stands as an important first boundary case between the scope of Rowling’s imagination and fans’ desires to fit within it. Adapting Ebony Elizabeth Thomas’ framework to name a ‘manumissive black fantastic’, I explore a method for observing modes of fan engagement steeped in racial grief and, coextensively, a method for engaging in racial grief through fandom. By way of demonstration, this article concludes with a short work of original fan fiction.